Blue Basin, Trinidad, B.W.I. - (:unkn) unknown (Muir Marshall and Co. Ltd.,[Trinidad and Tobago], 2011)
The postcard shows the magnificent Blue Basin Waterfall located in Diego Martin, a town in northwest Trinidad.
Colour: Sepia; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Diego Martin; Waterfalls--Trinidad and Tobago; Blue Basin Waterfall (Trinidad and Tobago)